Analysis of Digital Literacy Profile of Elementary School Students at SDN Jayamekar Padalarang in Technology-Based Learning - Rafli, Andi; Iriawan, Sandi Budi (International Conference on Elementary Education, 2025)
Digital literacy has become an essential 21st-century skill that students must possess to face the digital era. This study aims to analyze the digital literacy profile of elementary school students in the context of technology-based learning using a descriptive quantitative research design. The research sample consisted of 40 fifth-grade students from SDN Jayamekar, Padalarang District. The instrument used was a closed questionnaire with a Likert scale of 1-4 designed to measure 7 domains of digital literacy based on the UNESCO framework, including: access, manage, understand, integrate, evaluate, create, and communicate. The research results show that students overall digital literacy level reached 73%. Technical-operational domains demonstrated significant dominance with the access domain(access) obtaining the highest percentage of 78.95%, indicating that students already possess good abilities in accessing and operating digital devices. Conversely, creative-productive domains remain less dominant, as evidenced by the create domain (digital content creation) obtaining the lowest percentage of 64.58%, indicating that skills in producing digital content still need improvement. This gap betweentechnical and creative abilities constitutes the main finding of the research, showing that althoughelementary school students are competent in using technology, their ability to create and produce digitalcontent requires more attention in learning. The relevance of this research lies in identifying the gap instudents digital literacy competencies, enabling teachers to create learning processes that encourage digital creativity to comprehensively balance digital literacy competencies in accordance with 21st-century skills demands.